Status of the First Permanent Molars in Students from the José Antonio Saco Elementary School - Diosky Ferrer Vílchez; Ana Belkys Hernández Millán; Disney Tablada Peralta; Ana Ivis Betancourt García; Antonio Araujo Vílchez; Yenly Rodríguez Alonso (Universidad de las Ciencias Médicas de Cienfuegos, 2016)
Background: the first molars are among the first teeth affected by dental caries. Their premature loss leads to occlusion disorders. Objective: to determine the status of the first permanent molars in first-, fourth- and sixth- grade students from the Jose Antonio Saco elementary school in Cienfuegos. Methods: a cross-sectional study was conducted in a universe of 227 students treated at the Raúl González Pediatric Dental Clinic of the health area number 1 in Cienfuegos from October 2014 to March 2015. The variables analyzed were: age, sex, application of Love's index, oral health status, application of Clune's dent Results: females (50.2 %) and the 5-9 age groups (60.4 %) predominated. Dental caries were most commonly found in the left mandibular first molar (37.5 %) and most fillings were placed on the right mandibular first molar (35.2 %). A history of dental caries was the risk factor with the highest impact on both sexes and age groups, with values between 35 and 61 %. Conclusion: the status of the first permanent molars can be generally classified as favorable, which was demonstrated through Clone's index. A history of dental caries was a predisposing risk factor for the development of this condition; poor hygiene, presence of deep grooves and parental ignorance were also significant.